Preparation method and application of lattice-gap mixed RuO2 solid solution acidic oxygen evolution electrocatalyst

By preparing the lattice-gap mixed RuO2 solid solution acid oxygen evolution electrocatalyst, the problem of RuO2 structural degradation in an acidic environment is solved, and efficient and long-term stable catalytic effect of acid oxygen evolution reaction is achieved.

CN119615238APending Publication Date: 2025-03-14BEIJING INST OF TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510107056.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-23
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

In the prior art, RuO2 is prone to structural degradation in an acidic environment, difficult to achieve long-term stability, and the research on acidic oxygen evolution reaction catalysts is relatively lagging, making it difficult to develop stable and efficient catalysts.

Method used

The preparation method of a lattice-gap mixed RuO2 solid solution acidic oxygen evolution electrocatalyst is prepared by dissolving soluble ruthenium salt, high-valent metal salt, non-metal salt and molten salt medium in deionized water, and then quickly lyophilized after uniform mixing, so that the high-valent metal and non-metal elements are uniformly doped into the RuO2 lattice, and a highly uniform dispersed catalyst is prepared.

Benefits of technology

At a current density of 10mAcm-2, the overpotential of the catalyst is only 168mV, and the stability exceeds 500h. It has the dual advantages of high activity and long stability, and is suitable for the preparation and application of acidic OER electrocatalysts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119615238A_ABST
    Figure CN119615238A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a lattice-gap mixed RuO2 solid solution acidic oxygen evolution electrocatalyst. According to the RuO2 electrocatalyst and the preparation method thereof, high-valence metal is introduced into RuO2 unit cells at the same time to serve as a lattice substitution doping component, nonmetal serves as an interstitial doping component, and a lattice-interstitial mixed RuO2 solid solution structure is constructed, so that the activity and stability of the RuO2 electrocatalyst are remarkably improved. The preparation method comprises the following steps: dissolving soluble ruthenium salt, high-valence metal salt, non-metal salt and a molten salt medium in deionized water, and stirring to form a solution; the solution is freeze-dried to prepare a precursor, and then the precursor is subjected to heat treatment to obtain the lattice-gap mixed RuO2 solid solution acidic oxygen evolution electrocatalyst. According to the lattice-gap mixed RuO2 solid solution acidic oxygen evolution electrocatalyst prepared by the invention, the overpotential required by a catalytic oxygen evolution reaction under the current density of 10mA cm <-2 > can be as low as 168mV, and the electrocatalyst can continuously and stably work for more than 500h in an acidic environment, so that the application requirements of the acidic oxygen evolution electrocatalyst can be greatly met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of nano-catalytic materials, and in particular relates to a preparation method and application of a lattice-interstitial mixed RuO2 solid solution acidic oxygen evolution electrocatalyst. Background Art

[0002] As the demand for global sustainable development continues to increase, the application of electrochemical energy conversion technology in the field of new energy has become increasingly mature. Specifically, technologies such as electrocatalytic water decomposition to produce hydrogen, electrocatalytic carbon dioxide reduction, and electrocatalytic nitrogen reduction are generally regarded as potential ways to replace fossil energy, reduce carbon emissions, and obtain renewable fuels. Among them, hydrogen production by water electrolysis has attracted much attention due to its green and clean production model. However, in the process of water electrolysis, the oxygen evolution reaction occurring on the anode side involves a complex multi-electron transfer process with relatively slow kinetics, which often becomes the rate-limiting step of the reaction. Therefore, there is an urgent need to develop efficient oxygen evolution catalysts to increase the reaction rate, reduce energy consumption, and promote the large-scale application of water electrolysis hydrogen production technology.

[0003] Over the years, researchers have made significant progress in the field of alkaline oxygen evolution catalysts and developed many efficient and stable materials. However, alkaline systems are difficult to operate at high current densities (>1A / cm 2 ) conditions to meet actual needs. In contrast, acidic proton exchange membrane water electrolysis technology is suitable for high current density operation due to its high ionic conductivity, fast dynamic response and compact design, and is considered to be the key to future green hydrogen production. However, acidic environments have higher requirements for oxygen evolution catalysts. Currently, research on catalysts for acidic oxygen evolution reactions is still lagging behind, and the development of stable and efficient acidic oxygen evolution reaction catalysts remains an important research direction.

[0004] At present, acidic oxygen evolution reaction catalysts are mainly concentrated in precious metal oxides, such as RuO2 and IrO2. Among them, RuO2 has attracted attention due to its relatively low cost and high catalytic activity, but RuO2 is prone to structural degradation in an acidic environment and is difficult to achieve long-term stability. Therefore, designing and preparing RuO2-based acidic oxygen evolution reaction catalysts with both high activity and high stability is of both scientific significance and important practical application value. Summary of the invention

[0005] In order to solve the above problems, especially to address the deficiencies in the prior art, the present invention provides a method for preparing a lattice-interstitial mixed RuO2 solid solution acidic oxygen evolution electrocatalyst and its application to solve the above problems.

[0006] To achieve the above purpose, the technical method adopted by the present invention is as follows:

[0007] Step 1: dissolving a soluble ruthenium salt, a high-valent metal salt, a non-metallic salt and a molten salt medium in deionized water, and stirring to form a solution;

[0008] Step 2: After the solution obtained in step 1 is quickly frozen, it is placed in a freeze dryer for freeze drying;

[0009] Step 3: Place the freeze-dried precursor in a quartz boat, put it in a muffle furnace, and heat it to a specified temperature for heat treatment;

[0010] Step 4: After the heat treatment is completed, the solid product is cooled to room temperature, taken out, poured into deionized water for washing, and after multiple centrifugal washing and drying, a lattice-interstitial mixed RuO2 solid solution acidic oxygen evolution electrocatalyst is obtained.

[0011] The method for preparing the lattice-interstitial mixed RuO2 solid solution material provided by the present invention has a simple process and is convenient for industrial production. The prepared lattice-interstitial mixed RuO2 solid solution material is used as an electrocatalyst for catalyzing the oxygen separation reaction of water electrolysis. -2 At a current density of , the overpotential is 168 mV, and it can work stably for more than 500 h. It has the dual advantages of high activity and long stability, and is suitable for the preparation and application of acidic OER electrocatalysts.

[0012] Preferably, the soluble ruthenium salt is one or more of ruthenium chloride, ruthenium acetate, ruthenium acetylacetonate or potassium chlororuthenate.

[0013] Preferably, the soluble high-valent metal salt is one or more of sodium vanadate, vanadium chloride, chromium chloride, potassium dichromate, sodium dichromate, manganese chloride, potassium permanganate, osmium chloride, molybdenum chloride, ammonium molybdate, sodium molybdate, tungsten chloride, sodium tungstate, ammonium metamolybdate, ammonium metatungstate, sodium perrhenate, tantalum chloride, sodium tantalate, potassium tantalate, niobium chloride or sodium niobate.

[0014] Preferably, the soluble non-metallic salt is one or more of boric acid, sodium borate, sodium carbonate, potassium carbonate, sodium oxalate, ammonium nitrate, ammonium chloride, sodium phosphate, sodium sulfate, potassium sulfate, sodium fluoride, potassium fluoride, sodium chloride or potassium chloride.

[0015] Preferably, the molten salt medium is one or more of potassium nitrate, sodium nitrate, lithium nitrate, potassium chloride, sodium chloride or lithium chloride.

[0016] Preferably, the molar ratio of the soluble ruthenium salt to the high-valent metal salt is 10:1-9; the molar ratio of the soluble ruthenium salt to the non-metallic salt is 10:1-9; the mass ratio of the soluble ruthenium salt to the molten salt medium is 1:10-150.

[0017] Preferably, in step 2, the freeze-drying time is 10 to 50 hours.

[0018] Preferably, in step 3, the heat treatment is carried out at a heating rate of 1 to 10°C / min, the temperature is raised to 200 to 900°C, and the temperature is kept for 1 to 12 hours.

[0019] Preferably, in step 4, the specific process of centrifugal washing is: first centrifugally separating the mixed solution, collecting the product and repeatedly washing it with deionized water; repeating the centrifugal separation and washing process 1 to 10 times.

[0020] Preferably, in step 4, the rotation speed of each centrifugal separation is 3000-10000 rpm / min, and the duration of each centrifugal separation is 2-30 min.

[0021] Preferably, in step 4, the drying time is 10 to 50 hours.

[0022] The present invention also provides a lattice-interstitial mixed RuO2 solid solution acidic oxygen evolution electrocatalyst prepared by any of the above technical solutions.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] 1: The present invention proposes a lattice-interstitial mixed RuO2 solid solution electrocatalyst, which is prepared by dissolving a soluble ruthenium salt, a high-valent metal salt, a non-metallic salt and a molten salt medium in deionized water, uniformly mixing and then quickly freeze-drying, so that the high-valent metal and non-metallic elements are uniformly doped into the RuO2 lattice, and a highly uniformly dispersed catalyst is prepared.

[0025] 2: Tests in the acidic oxygen evolution reaction show that the catalyst of the present invention has a -2 The overpotential at the current density is only 168mV, and the stability is more than 500h. Under the same conditions, the overpotential of the undoped RuO2 catalyst is as high as 245mV and it is deactivated within 15h. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0027] Figure 1 This is the X-ray diffraction spectrum of the lattice-interstitial mixed RuO2 solid solution obtained in Example 1.

[0028] Figure 2 This is a scanning electron microscope image of the lattice-interstitial mixed RuO2 solid solution obtained in Example 1.

[0029] Figure 3 This is the X-ray photoelectron spectrum of the lattice-interstitial mixed RuO2 solid solution obtained in Example 1.

[0030] Figure 4 It is a high-angle annular dark field scanning transmission electron microscope image of the lattice-interstitial mixed RuO2 solid solution obtained in Example 1 and a line scanning intensity distribution diagram of the marked area.

[0031] Figure 5 This is a comparison diagram of the scanning linear voltammetry curves of the lattice-interstitial mixed RuO2 solid solution obtained in Example 1 and the undoped RuO2 catalyst prepared in Comparative Example 1.

[0032] Figure 6 The lattice-interstitial mixed RuO2 solid solution obtained in Example 1 is 10 mA cm -2 Stability test diagram under current density. DETAILED DESCRIPTION

[0033] Those skilled in the art will appreciate that the following embodiments are only preferred embodiments of the present invention, which are used to illustrate the technical solutions of the present invention and do not constitute limitations of the present invention. Without departing from the spirit and principles of the present invention, any modification, equivalent replacement or improvement is included in the protection scope of the present invention.

[0034] Example 1

[0035] This embodiment prepares a lattice-interstitial mixed RuO2 solid solution acidic oxygen evolution electrocatalyst, which specifically includes the following steps:

[0036] Step 1: Weigh 20g of sodium chloride and dissolve it in 20mL of deionized water, stirring until it is completely dissolved to form a solution; add 1g of ruthenium chloride, 0.3g of tungsten chloride and 0.5g of ammonium nitrate to the solution, and continue stirring until the solution is uniform.

[0037] Step 2: The uniform solution obtained in step 1 is placed in liquid nitrogen for rapid freezing, and then placed in a freeze dryer for freeze drying for 30 hours.

[0038] Step 3: Place the freeze-dried precursor in a quartz boat, put it into a muffle furnace, and oxidize it in an air environment at 600°C for 8 hours. Step 4: After the temperature of the muffle furnace is cooled to room temperature, take out the quartz boat containing the oxidized solid product, add deionized water and disperse it for 30 minutes to obtain a mixed solution. The mixed solution is centrifuged, the product is collected and washed with deionized water, and the centrifugation and washing process is repeated 10 times. Finally, the obtained product is dried for 30 hours to obtain a lattice-interstitial mixed RuO2 solid solution acidic oxygen evolution electrocatalyst. Among them, the speed of each centrifugation is 6000rpm / min, and the duration of each centrifugation is 2min. Figure 1 This is the X-ray diffraction spectrum of the lattice-interstitial mixed RuO2 solid solution acidic oxygen evolution electrocatalyst obtained in Example 1. It can be observed that the diffraction peaks of the lattice-interstitial mixed RuO2 solid solution acidic oxygen evolution electrocatalyst obtained in Example 1 are consistent with the RuO2#PDF standard card, and no diffraction peaks of other oxides were found.

[0039] Figure 2 This is a scanning electron microscope image of the lattice-interstitial mixed RuO2 solid solution acidic oxygen evolution electrocatalyst prepared in Example 1, from which it can be observed that the catalyst particles are uniform in size.

[0040] Figure 3 This is the X-ray photoelectron spectrum of the lattice-interstitial mixed RuO2 solid solution acidic oxygen evolution electrocatalyst prepared in Example 1, from which the appearance of W4f and N1s can be observed, which confirms that W and N are successfully doped into RuO2.

[0041] Figure 4 The high-angle annular dark-field scanning transmission electron microscope image of the lattice-interstitial mixed RuO2 solid solution acidic oxygen evolution electrocatalyst prepared in Example 1 and the line scanning intensity distribution diagram of the marked area. It can be observed that there are differences in the brightness of the metal sites in the same crystalline phase region, indicating that the W element has been successfully doped into the RuO2 lattice. Combined with the line scanning intensity distribution results of the marked area, it can be further confirmed that the W atoms enter RuO2 in the form of lattice doping. At the same time, isolated N atoms are also observed in the lattice gaps, and their imaging contrast is weak, which is consistent with the characteristics of light elements with low atomic numbers. Based on the above analysis results, it can be seen that the W element enters the RuO2 lattice in the form of lattice doping, while the N element is distributed in the RuO2 lattice gaps in the form of interstitial doping.

[0042] Comparative Example 1

[0043] Comparative Example 1 prepares an undoped RuO2 catalyst. The preparation process is different from that of Example 1, except that tungsten chloride and ammonium nitrate are not added in step 1; the other steps are the same.

[0044] The oxygen evolution performance of the lattice-interstitial mixed RuO2 solid solution acidic oxygen evolution electrocatalyst prepared in Example 1 and the undoped RuO2 catalyst prepared in Comparative Example 1 were tested, specifically:

[0045] 10 mg of catalyst powder was added to 1000 μL of mixed solution (containing 950 μL of anhydrous ethanol and 50 μL of 5 wt% Nafion), and the mixture was evenly dispersed by ultrasonic treatment to obtain catalyst slurry. 30 μL of catalyst slurry was evenly sprayed on a 1 cm 2 The anode was prepared on the hydrophilic carbon paper after drying to form the anode for the oxygen evolution reaction in water electrolysis.

[0046] In the three-electrode system, carbon paper loaded with catalyst was used as the anode, mercury / mercurous sulfate electrode was used as the reference electrode, carbon rod was used as the counter electrode, and 0.5M sulfuric acid was used as the electrolyte solution. Linear sweep voltammetry test and electrochemical activity area normalization test were performed using CHI760E electrochemical workstation under normal temperature and pressure conditions.

[0047] The results of the linear sweep voltammetry test are as follows: Figure 5 As shown in the figure, it can be seen that the lattice-interstitial mixed RuO2 solid solution acidic oxygen evolution electrocatalyst obtained in Example 1 can reach 10mAcm at an overpotential of 168mV. -2 The current density is 2.34 W, which is 0.18 W. Compared with the undoped RuO2 catalyst in Comparative Example 1, the catalytic activity is significantly improved.

[0048] The carbon paper of the lattice-interstitial mixed RuO2 solid solution acidic oxygen evolution electrocatalyst prepared in Example 1 was immersed in an electrolyte, and its stability was tested by constant current method. The obtained potential change curve with time is shown in FIG. Figure 6 The results show that at 10mAcm -2 At a current density of , the catalyst can operate stably for more than 500 h, fully demonstrating its excellent long-term stability.

[0049] Example 2

[0050] Step 1: Weigh 30 g of lithium chloride and dissolve it in 50 mL of deionized water, stirring until it is completely dissolved to form a solution; add 1 g of ruthenium chloride, 0.5 g of sodium perrhenate and 0.5 g of sodium fluoride to the solution, and continue stirring until the solution is uniform.

[0051] Step 2: The uniform solution obtained in step 1 is placed in liquid nitrogen for rapid freezing, and then placed in a freeze dryer for freeze drying for 10 hours.

[0052] Step 3: Place the freeze-dried precursor in a quartz boat, put it into a muffle furnace, and oxidize it in an air environment at 800°C for 6 hours. Step 4: After the temperature of the muffle furnace is cooled to room temperature, take out the quartz boat containing the oxidized solid product, add deionized water and disperse it for 10 minutes to obtain a mixed solution. The mixed solution is centrifuged, the product is collected and washed with deionized water, and the centrifugation and washing process is repeated 6 times. Finally, the obtained product is dried for 25 hours to obtain a lattice-interstitial mixed RuO2 solid solution acidic oxygen evolution electrocatalyst. Among them, the speed of each centrifugation is 8000rpm / min, and the duration of each centrifugation is 2 minutes.

[0053] Example 3

[0054] Step 1: Weigh 20 g of potassium nitrate and dissolve it in 20 mL of deionized water, stirring until it is completely dissolved to form a solution; add 2 g of ruthenium acetylacetonate, 0.9 g of tungsten chloride and 0.8 g of sodium fluoride to the solution, and continue stirring until the solution is uniform.

[0055] Step 2: The uniform solution obtained in step 1 is placed in liquid nitrogen for rapid freezing, and then placed in a freeze dryer for freeze drying for 20 hours.

[0056] Step 3: Place the freeze-dried precursor in a quartz boat, put it into a muffle furnace, and oxidize it in an air environment at 600°C for 8 hours. Step 4: After the temperature of the muffle furnace is cooled to room temperature, take out the quartz boat containing the oxidized solid product, add deionized water and disperse it for 30 minutes to obtain a mixed solution. The mixed solution is centrifuged, the product is collected and washed with deionized water, and the centrifugation and washing process is repeated 10 times. Finally, the obtained product is dried for 30 hours to obtain a lattice-interstitial mixed RuO2 solid solution acidic oxygen evolution electrocatalyst. Among them, the speed of each centrifugation is 6000rpm / min, and the duration of each centrifugation is 2min.

[0057] Example 4

[0058] Step 1: Weigh 20g of sodium chloride and dissolve it in 20mL of deionized water, stirring until it is completely dissolved to form a solution; add 1g of ruthenium chloride, 0.3g of tungsten chloride and 0.5g of ammonium nitrate to the solution, and continue stirring until the solution is uniform.

[0059] Step 2: The uniform solution obtained in step 1 is placed in liquid nitrogen for rapid freezing, and then placed in a freeze dryer for freeze drying for 30 hours.

[0060] Step 3: Place the freeze-dried precursor in a quartz boat, put it into a muffle furnace, and oxidize it in an air environment at 800°C for 2 hours. Step 4: After the temperature of the muffle furnace is cooled to room temperature, take out the quartz boat containing the oxidized solid product, add deionized water and disperse it for 30 minutes to obtain a mixed solution. The mixed solution is centrifuged, the product is collected and washed with deionized water, and the centrifugation and washing process is repeated 10 times. Finally, the obtained product is dried for 30 hours to obtain a lattice-interstitial mixed RuO2 solid solution acidic oxygen evolution electrocatalyst. Among them, the speed of each centrifugation is 6000rpm / min, and the duration of each centrifugation is 2min.

[0061] Example 5

[0062] Step 1: Weigh 10 g of potassium chloride and dissolve it in 20 mL of deionized water, stirring until it is completely dissolved to form a solution; add 1 g of ruthenium acetate, 0.8 g of potassium permanganate and 0.5 g of sodium borate to the solution, and continue stirring until the solution is uniform.

[0063] Step 2: The uniform solution obtained in step 1 is placed in liquid nitrogen for rapid freezing, and then placed in a freeze dryer for freeze drying for 10 hours.

[0064] Step 3: Place the freeze-dried precursor in a quartz boat, put it into a muffle furnace, and oxidize it in an air environment at 700°C for 5 hours. Step 4: After the temperature of the muffle furnace is cooled to room temperature, take out the quartz boat containing the oxidized solid product, add deionized water and disperse it for 20 minutes to obtain a mixed solution. The mixed solution is centrifuged, the product is collected and washed with deionized water, and the centrifugation and washing process is repeated 10 times. Finally, the obtained product is dried for 20 hours to obtain a lattice-interstitial mixed RuO2 solid solution acidic oxygen evolution electrocatalyst. Among them, the speed of each centrifugation is 5000rpm / min, and the duration of each centrifugation is 2min.

[0065] The present invention illustrates its principles and implementation methods through specific embodiments. The description of these embodiments is intended to help understand the method of the present invention and its core ideas, including the best implementation methods, and to enable those skilled in the art to practice the present invention, including manufacturing and using related devices or systems, and implementing combined methods. It should be pointed out that for those of ordinary skill in the art, various improvements and modifications can be made to the present invention without departing from the core ideas and principles of the present invention. These improvements and modifications also belong to the scope of protection of the claims of the present invention. The scope of protection of the present invention is defined by the claims and includes other embodiments that can be thought of by those skilled in the art. If the structural elements of these embodiments are the same as the structural elements described in the claims, or there are only equivalent structural elements with no substantial differences, then these embodiments also belong to the scope of protection of the claims of the present invention.

Claims

1. A lattice-interstitial mixed RuO2 solid solution acidic oxygen evolution electrocatalyst, characterized in that: The steps include: Step 1: dissolving a soluble ruthenium salt, a high-valent metal salt, a non-metallic salt and a molten salt medium in deionized water, and stirring to form a solution; Step 2: After the solution obtained in step 1 is quickly frozen, it is placed in a freeze dryer for freeze drying; Step 3: Place the freeze-dried precursor in a quartz boat, put it in a muffle furnace, and heat it to a specified temperature for heat treatment; Step 4: After the heat treatment is completed, the solid product is cooled to room temperature, taken out, poured into deionized water for washing, and after multiple centrifugal washing and drying, a lattice-interstitial mixed RuO2 solid solution acidic oxygen evolution electrocatalyst is obtained.

2. The method for preparing a lattice-interstitial mixed RuO2 solid solution acidic oxygen evolution electrocatalyst according to claim 1, characterized in that: In step 1, the soluble ruthenium salt is one or more of ruthenium acetate, ruthenium chloride, ruthenium acetylacetonate or potassium chlororuthenate.

3. The method for preparing a lattice-interstitial mixed RuO2 solid solution acidic oxygen evolution electrocatalyst according to claim 1, characterized in that: In step 1, the metal cation of the soluble high-valent metal salt solution is: V 5+ Cr 6+ , Mn 6+ , Os 6+ 、Mo 6+ , W 6+ 、Re 6+ 、 5+ or Nb 5+ One or more of the .

4. The method for preparing a lattice-interstitial mixed RuO2 solid solution acidic oxygen evolution electrocatalyst according to claim 1, characterized in that: In step 1, the non-metal anion of the soluble non-metal salt solution is BO3 3- 、CO3 2- 、C2O4 2- 、NO3 - PO4 3- 、SO4 2- 、F - or Cl - One or more of the .

5. The method for preparing a lattice-interstitial mixed RuO2 solid solution acidic oxygen evolution electrocatalyst according to claim 1, characterized in that: In step 1, the molten salt medium is an alkali metal nitrate or hydrochloride, such as one or more of potassium nitrate, sodium nitrate, lithium nitrate, potassium chloride, sodium chloride or lithium chloride.

6. The method for preparing a lattice-interstitial mixed RuO2 solid solution acidic oxygen evolution electrocatalyst according to claim 1, characterized in that: In step 1, the molar ratio of the soluble ruthenium salt to the high-valent metal salt is 10:1-9; the molar ratio of the soluble ruthenium salt to the non-metallic salt is 10:1-9; and the mass ratio of the soluble ruthenium salt to the molten salt medium is 1:10-150.

7. The method for preparing a lattice-interstitial mixed RuO2 solid solution acidic oxygen evolution electrocatalyst according to claim 1, characterized in that: In step 2, the freeze-drying time is 10 to 50 hours.

8. The method for preparing a lattice-interstitial mixed RuO2 solid solution acidic oxygen evolution electrocatalyst according to claim 1, characterized in that: In step 3, the heat treatment is carried out at a heating rate of 1 to 10°C / min, the temperature is raised to 200 to 900°C, and the temperature is kept for 1 to 12 hours.

9. The method for preparing a lattice-interstitial mixed RuO2 solid solution acidic oxygen evolution electrocatalyst according to claim 1, characterized in that: In step 4, the drying time is 10 to 50 hours.

10. The lattice-interstitial mixed RuO2 solid solution acidic oxygen evolution electrocatalyst prepared by the preparation method according to any one of claims 1 to 9.

11. The use of a lattice-interstitial mixed RuO2 solid solution acidic oxygen evolution electrocatalyst according to claim 10, characterized in that: The lattice-interstitial mixed RuO2 solid solution acidic oxygen evolution electrocatalyst is used in the production of hydrogen by electrolysis of water.

Citation Information

Cited By

  • Ti-RuO2 acidic oxygen evolution catalyst based on strain modulation strategy and preparation method thereof

    CN120291145A